Tailoring of Atlantic salmon (Salmo salar L.) flesh lipid composition and sensory quality by replacing fish oil with a vegetable oil blend - Torstensen, Bente E; Bell, J Gordon; Rosenlund, Grethe; Henderson, R James; Graff, Ingvild E; Tocher, Douglas R; Lie, Oyvind; Sargent, John R (Journal of Agricultural and Food Chemistry, 2005)
Atlantic salmon (Salmo salar L.) juveniles were fed either 100% fish oil (FO), 75% vegetable oil (VO) or 100% VO throughout their life cycle to harvest weight followed by a finishing diet period when all groups were fed 100% FO. The two experimental VO diets were tested at two different locations against the same control diet (100% FO) (Scotland and Norway). The VO blend was composed of rapeseed oil, palm oil and linseed oil using capelin oil as a control for fatty acid class compositions. Flesh fatty acid profiles were measured regularly throughout the experiment, with the times of sampling determined by changes in pellet size/lipid content and fish life stage. Growth and mortality rates were not significantly affected by dietary fatty acid compositions throughout the life cycle, except during the seawater winter period in Norway when both growth and protein utilisation were increased in salmon fed 100% VO compared to 100% FO. Flesh fatty acid composition was highly influenced by that of the diet, and after the finishing diet period the weekly recommendations of VLCn-3 PUFA for human health were 80 % and 56 % satisfied by a 200 g meal of 75% VO and 100% VO flesh, respectively. No effect on flesh astaxanthin levels was observed in relation to changing dietary oil sources. Sensory evaluation showed only minor differences between salmon flesh from the dietary groups although prior to the finishing diet period, flesh from 100% VO had less rancid and marine characteristics, and was preferred over flesh from the other dietary groups by a trained taste panel. After the finishing diet period the levels of typical vegetable oil fatty acids in flesh were reduced whereas those of VLCn-3 PUFA increased to levels comparable with a 100% FO fed salmon. No differences in any of the sensory characteristics were observed between dietary groups. By blending VO’s to provide balanced levels of dietary fatty acids up to 100% of the fish oil can be replaced by the VO blend without compromising growth or flesh quality. At the same ...